Wireless Personal Communications Simulation and Complexity - A. M. El-Bendary, Mohsen (Signals and Communication Technology,, 2018)
This book introduces wireless personal communications from the point of view of wireless communication system researchers. Existing sources on wireless communications put more emphasis on simulation and fundamental principles of how to build a study model. In this volume, the aim is to pass on to readers as much knowledge as is essential for completing model building of wireless communications, focusing on wireless personal area networks (WPANs). This book is the first of its kind that gives step-by-step details on how to build the WPANs simulation model. It is most helpful for readers to get a clear picture of the whole wireless simulation model by being presented with many study models. The book is also the first treatise on wireless communication that gives a comprehensive introduction to data-length complexity and the computational complexity of the processed data and the error control schemes. This volume is useful for all academic and technical staff in the fields of telecommunications and wireless communications, as it presents many scenarios for enhancing techniques for weak error control performance and other scenarios for complexity reduction of the wireless data and image transmission. Many examples are given to help readers to understand the material covered in the book. Additional resources such as the MATLAB codes for some of the examples also are presented.